Kesiapan Guru dalam Mengimplementasikan Kurikulum Merdeka di Mi Muhammadiyah Toyareka Kecamatan Kemangkon Kabupaten Purbalinggga - Ameliya, Sekar Ayu; Gunawan, Yosi Intan Pandini (Lembaga Intelektual Muda (LIM) Maluku, 2025)
The aim of this study is to analyze teacher readiness in implementing the independent curriculum at MI Muhammadiyah Toyareka in terms of attitude readiness, cognitive readiness, and behavioral readiness. The research uses a qualitative descriptive approach, with data collection methods including observation, interviews, and documentation. The subjects of the study include the school principal, teachers, and students of grades I, II, IV, and V. Data analysis techniques involve data reduction, data presentation, and conclusion drawing. The research results show that the teachers at Muhammadiyah Toyareka MI are prepared to implement the independent curriculum, but not fully, as seen from three indicators of readiness: attitude readiness, where the teachers have interest and motivation as a feeling of enjoyment and a strong determination to improve results in implementing the independent curriculum, there is also mapping of teacher readiness, cognitive readiness, where teachers have understood the concept of the independent curriculum, lesson planning, implementation, and assessment, but not fully. Behavioral readiness, teachers are already capable in assessing learning, but there are still obstacles in planning, implementation, and the use of facilities and infrastructure in learning, which requires training.